THE SOCIAL-PEDAGOGICAL FOUNDATIONS OF SHAPING NATIONAL IDENTITY IN STUDENTS THROUGH SPORTS - Qosimov Akmal Nasridinovich (Journals Park Publishing, 2025)
This article is dedicated to studying the importance of sports in the formation of national identity. National identity encompasses the unique characteristics, traditions, and values of each nation, playing a significant role in social life. The use of sports in shaping national identity among students is crucial for their physical, spiritual, and social development. The article presents thoughts on the concept of national identification, the individual's sense of being part of a national society, and the unifying role of sports activities.
Keywords: National identity, sport, physical education, spiritual development, social development, national values, traditions, education and upbringing, Uzbekistan development strategy, personnel training, innovative education, preschool education, universal values, globalization, migration processes.